Keputusan Konsumen dalam Melakukan Pembelian di Coffe Shop - Humaidi, Edy; Analianasari, Analianasari; Fatih, Cholid (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
The purpose of this study was to analyze the factors that influence consumer decisions in making purchases at coffee shops, this study was conducted in three coffee shops in Bandar Lampung, the determination of the three coffee shops was done purposively with a total sample of 60 samples. This research was conducted from May to July. The data analysis method in this study used Structural Equation Modeling (SEM). SEM analysis in this study uses the SEM PLS (Partial Least Square) technique. The results of the analysis show that of the five variables that are thought to influence purchasing decisions, only one variable has a significant effect, namely the price variable with P-values of 0.013 (<0.05).